La fugitiva: Personal Liberty, Exile and Indifference - Vargas Vargas, José Ángel (2017)
The novel La fugitiva, by Sergio Ramírez-Mercado, is analyzed to determine how this author fictionalizes the life of Yolanda Oreamuno. Three main topics are examined: personal freedom, exile, and indifference. The metaphorical elaboration of the character Amanda Solano is explored, focusing on the concept of personal freedom, as associated with exile. Furthermore, the subjective and contextual peculiarities that generate it are studied. Finally, we address the issue of indifference, related to power and how Costa Rica perceives and values culture.